(untitled) (Dentika: Dental Journal, 2009)
Fabrication of prostheses must be planned and designed to fit harmoniously with the complexity of the neuromuscular system of the patient, the temporomandibular joints and supporting structures of the teeth. Any occlusal interference from the prostheses would invade the systems and caused various problems to the patient. The aim of this study was to evaluate the occlusion of 3-unit conventional bridges prior to cementation. All bridges that scheduled for cementation was noted. Before the occlusal examination was performed, the retainers were examined to ensure good marginal fit and have adequate interproximal contact with adjacent teeth. Occlusal examination was performed using articulating foil with the thickness of 8Âµm, Millerâ€™s forceps and thickness gauge. From 33 bridges identified, 93.9% were qualified for occlusal examination. Most of the retainers and pontics showed multiple high spots. From 62 retainers and 31 pontics, 213 occlusal contacts were obtained, with 25.8% on cuspal inclinations, 24.4% presented with high spots on marginal ridges and 11.7% on cuspal tips. The thickness of the high spots ranges from 0.5-3.6mm. High occlusion could be resulted from various factors such as inadequate tooth preparation and lack on the usage of semiadjustable articulator. Occlusal examination has to be performed prior to bridge cementation to ensure comfort during functioning and health of the hard and soft tissues.